Effects of Spartina alterniflora invasion on the benthic invertebrate community in intertidal wetlands. Issue 3 (8th March 2022) - Lu, Kangle; Han, Guangxuan; Wu, Haitao
Abstract: Exotic species invasions have profound effects on native ecosystems, with the ecological effects of non‐native plants being especially pervasive. We investigated the impacts of a plant invasion on benthic invertebrate assemblages in intertidal wetlands of the Yellow River Delta, comparing benthic communities associated with exotic Spartina alterniflora against those associated with native plants ( Tamarix chinensis, Suaeda salsa, and mudflat). Our study surprisingly found that the density, diversity, and richness of benthic invertebrates associated with S. alterniflora were higher than with native habitats. Multivariate analysis also revealed that the structure of benthic invertebrates in S. alterniflora habitats was different than in T. chinensis and mudflat habitats. The structure of invertebrates associated with the invasive S. alterniflora and native S. salsa was more similar, although the dominant species differed. Indicator species analyses indicated that each habitat was characterized by unique taxa. S. alterniflora invasion increased the beta diversity of the community, with the species turnover component being of most importance. Mollusks were most likely to be influenced by Spartina invasions. Given the extent of the S. alterniflora invasion in the Yellow River Delta, altered benthic invertebrate communities will likely have important implications for the ecology of the intertidal wetland ecosystems and deserve increased attention.